Жандармы против «Совести»: Эпизод борьбы органов политической полиции с панисламистским движением в Таврической губернии - Пасечников, И.А. (Культура народов Причерноморья, 2013)
В статье рассматривается малоизученная страница истории противостояния органов политической полиции Таврической губернии и зарождавшегося национального крымскотатарского движения. Основное внимание сосредоточено на этапах развития прообраза первой партии крымских татар – организации «Совесть», а также на деятельности чинов Таврического губернского жандармского управления и Севастопольского охранного отеделения, направленной на её ликвидацию. Предпринята попытка определения роли панисламистского сообщества в историческом процессе на территории Крыма в начале XX века. У статті розглядається маловивчена сторінка історії протистояння органів політичної поліції Таврійської губернії і зародження національного кримськотатарського руху. Основна увага зосереджена на етапах розвитку прообразу першої партії кримських татар – організації «Совість», а також на діяльності чинів Таврійського губернського жандармського управління та Севастопольського охоронного відділення, спрямованої на її ліквідацію. Зроблена спроба визначення ролі панісламістського товариства в історичному процесі на території півострова на початку XX століття. The article examines the byway page of the political history of Crimea. Special attention was paid to the development of the prototype of the first Crimean Tatar national party – the organization «Conscience». An attempt to define the role of the pan-Islamic group in the historical process in the Crimea at the beginning of XX century was made. Also the activities of employees of the Taurida Governorate Gendarme Department and Sevastopol Guard department was deeply analyzed. The reason of the confrontation between two parties was the oppression of the religious schools of the Crimean Tatars by the Russian government, as well as ideas about cultural and national revival of the nation. The leading role in the «Conscience» belonged to the teachers and intellectuals, who partially professed social-democratic views. They also supported the idea of the revival of the Crimean Khanate and the alliance with the Turkey. The main task of the gendarmerie was the counteraction to any revolutionary or anti-government movements. With the help of the secret agents the surveillance of many members of the secret organization has been made. However, the sudden manifestation of the activity of the political movement among the Crimean Tatars, the lack of language skills and the lack of special agents caused great difficulties. This explains the failures of the police. In the article the little-known sources and archival documents had been used.